How do dinosaurs Say I'm mad? - Yolen, Jane; Teague, Mark (New York, N.Y. : The Blue Sky Press, 2013)
Illustrations and rhyming text explore some of the things that dinosaurs might do when they are angry--and how they should control their tempers.
Keywords: Dinosaurs -- Juvenile fiction; Anger -- Juvenile fiction; Temper tantrums -- Juvenile fiction; Stories in rhyme; Behavior -- Fiction; Dinosaurs -- Fiction; Anger -- Fiction; Emotions -- Fiction